Cohort Fertility Trends and Religion Affiliation in Latin America: a Glimpse Through Time - Lima, Everton Emanuel Campos de (Journal of religion and demography, 2019)
We analyze cohort fertility by religion and education in Latin America from periods previous to the general decline in period fertility in 1950s. We reconstruct cohort fertility and parity progression ratios of women born in 1930-1970 in a number of countries in the region, Brazil, Chile, Mexico, Paraguay and Peru. Our main aim is to understand the past developments of cohort fertility in the course of fertility transition in Latin America and to assess the role of religious affiliation, as well as to understand these developments controlling for a number of socioeconomic characteristics. We also seek to grasp if religion becomes more or less important with rising school levels and human capital over time.